Effect of dynamic versus static stretching in the warm-up on hamstring flexibility - Silveira, G.; Sayers, M.; Waddington, G. (The Sport Journal, 2011)
Abstract Recent studies have questioned the benefits of static stretching in the sports warm-up. The purpose of our research was to examine the acute effect of static and dynamic stretching in the warm-up, on hamstring flexibility using an intervention study design. Hamstring flexibility was measured using modifications of the Straight Leg Raise test to measure hip flexion range of motion in degrees. The reliability of the test setup was determined in a separate study (n=33), the results of which were also utilised to establish the relationship between static and dynamic SLR tests. There was a significant difference between flexibility measured by the Static-passive and the Dynamic-supine SLR test (p < .05); hence, these were utilised to assess static and dynamic flexibility, respectively, in the intervention study.